Digitomotography in children with oro‐facial dysfunction (OFD, oro‐facial myofunctional disorders) and childhood apraxia of speech (CAS). (3rd May 2021) - Stahl, Friederike; Pollex, Dörte; Mathmann, Philipp; Weinhold, Leonie; Rohrbach, Saskia
Abstract: Background: Oro‐facial dysfunctions (OFDs; oro‐facial myofunctional disorders) in children and childhood apraxia of speech (CAS) often cause severe problems in articulation, chewing, swallowing and oral posture. Objectives: Pathognomonic symptoms could yet not be identified, but central problems in planning, programming, timing and automating oro‐facial, as well as other fine motor skills, are assumed to be affected. Methods: To investigate the nature of motor and coordinative deficits in OFD and CAS, digitomotography was applied. The testing focused on recording frequency, force, rhythm and regularity of the index finger including speeded and metronome tapping tasks. 25 children with OFD (7 girls and 18 boys, age 7.9 ± 2.3) and 5 children with CAS (0 girls and 5 boys, age 7.6 ± 2.3), and 31 healthy controls (12 girls and 19 boys, age 9.3 ± 2.2) were tested. Statistical significance was accepted at α = 0.05. ANOVA test, non‐parametric Mann‐Whitney U test, Kruskal‐Wallis test and Spearman's rank correlation coefficient were used. Results: Cross‐sectional data revealed consistent significant differences between children with OFD and healthy controls concerning frequency, force, rhythm and regularity of index finger tapping. Individuals with CAS showed particularly low results. Tapping results correlated with disease burden. Conclusion: These findings support that underlying superordinated sensorimotor deficits exist. This may help phenotyping and influence diagnostical and therapeutical approaches. Abstract : Orofacial dysfunctions (OFD) in children and childhood apraxia of speech (CAS) often cause severe problems in articulation, chewing, swallowing and oral posture. Pathognomonic symptoms could yet not be identified. To investigate the nature of motor and coordinative deficits in OFD and CAS, digitomotography was applied. Cross‐sectional data revealed consistent significant differences between children with OFD and healthy controls. Individuals with CAS showed particularly low results.